The Limitation Period for Actions upon a Judgement and Execution Proceedings in Malaysia - Balan, Sujata (Journal of Malaysian and Comparative Law, 2012)
This article examines the legal position concerning an important aspect of the law on limitation periods in West Malaysia, namely, the limitation period for actions on a judgment found in section 6(3) of the Limitation Act 1953. It will be demonstrated that the operation and effect of section 6(3) is not free legal conundrums and this may cause difficulties for litigants in Malaysia. This article will argue that the application of this statutory provision is complex and uncertain and therefore reform is unnecessary.